3D bicontinuous SnO2/TiO2 core/shell structures for highly efficient organic dye-sensitized solar cell electrodes. Issue 78 (4th August 2016) - Cho, Chang-Yeol; Baek, Sujin; Kim, Kiwon; Moon, Jun Hyuk
Abstract : SnO2 /TiO2 core/shell hybrid structures with a 3D bicontinuous morphology were demonstrated as an electrode for dye-sensitized solar cells. Abstract : A photoelectrode for high performance photon-to-electron conversion devices has been developed with various material and structural aspects. For this purpose, one facile approach is introducing hybrid nanostructures. Here, we demonstrated SnO2 /TiO2 core/shell hybrid structures with a 3D bicontinuous morphology. We evaluated the effect of the electrode film thickness and the TiO2 shell thickness on the photovoltaic properties using photocurrent–voltage measurements and intensity-modulated photovoltage/photocurrent spectroscopy. As the film and the shell thicknesses increase, we observe a decrease in the charge collection efficiency, whereas the amount of dye adsorbed increases. At the optimum conditions, we obtain the highest photocurrent density of 19.06 mA cm −2 and a conversion efficiency of 8.21% with a 12 μm-thick film and 180 nm-thick shell electrode for dye-sensitized solar cells. The 3D bicontinuous SnO2 /TiO2 core/shell electrode is compared with the TiO2 /TiO2 electrode to evaluate the effect of the SnO2 core on the photovoltaic properties, and the presence of the SnO2 core enhances the trap-free charge transport mode and significantly enlarges the charge diffusion length by up to 5 times. We believe these results show that the 3D bicontinuous core/shell electrode may be coupled with other sensitizing dyes or quantum dots, as well as redox ions or hole transport materials, to obtain highly efficient photovoltaic or photoelectrochemical devices.